Effect of residence time on characteristics of torrefied sawdust produced from gmelina arborea (roxb) wood (2022)
Biomass feedstock remains a critical ingredient in all densification studies and the process conditions under which these materials were produced are significant to its performance. Conventionally, feedstocks are utilized in briquetting without major technological processing which is consequential on product characteristics. In this study, sawdust of Gmelina arborea subjected to thermochemical pre-treatment conditions was analysed and characteristics were compared with untreated material. Materials and Methods: Untreated sawdust of Gmelina arborea wood obtained from a sawmill in Ishiagu was torrefied at three residence times of 30 min, 45 and 60 min at a temperature of 250EC in a batch reactor and the products were characterized to determine their physical and chemical characteristics. Results: The particle-size distribution of untreated sawdust showed greater proportions of coarse and fine pin particles (58.03%) and (38.00%), respectively, requiring no grind with a mean particle density of 159.30±0.02. The proximate analysis of untreated sawdust at 7.78% moisture content revealed a volatile matter content of 72.93, 2.19% ash content and 17.10% carbon content. The proximate analysis of torrefied samples revealed a significant loss in volatile matter contents to 21.02% as residence time increased to 60 min, the fixed carbon increased from 17.10-65.38% and calorific values from 17.38 MJ kgG1 for raw sawdust to 26.28 MJ kgG1 as residence time increases. Reduction in volatile matter contents increased the energy values of torrefied sawdust. Conclusion: Thermochemical pretreatment of the feedstock significantly increase the material fixed carbon content and energy values of the Torrefied sample, reduced the volatile matter-the smoke-generating component of sawdust considerably and improved the product’s characteristics in briquetting.